Din manuscrisele inedite ale Arhiepiscopului Teofil Herineanu al Clujului: Predică pentru însoțitori la sfințirile de preoți - Rojneac, Vasile (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The present material makes available to researchers and those interested in the theological work of Archbishop Teofil Herineanu of Vad, Feleac and Cluj an unedited sermon, composed by the Diocesan Bishop of Cluj for priest ordinations. The homily, very thoroughly scripturally argued, sheds light on the sacramental work of the bishop and the priest within the Christian community. We mention the fact that this sermon is preserved, in a single copy, in the Archives of the Archdiocese of Vad, Feleac and Cluj, in the Collection of Archbishop Teofil Herineanu, Manuscripts section.